How Safety Awareness Affects Safety Citizenship Behavior: The Safety Motivation Mediation Perspective - Andjar, Wibawanti; Sanny, Lim; Siahaan, Denny; Pantja Djati, Sundring (Dinasti International Journal of Economics, Finance & Accounting, 2025)
The ship crew's safety citizenship behavior (SCB) is essential for protecting shipping. Based on the perspectives of safety awareness and motivation, this research aims to examine the SCB issue that mariners encounter while working on passenger ships. This investigation endeavors to assess the impact of safety awareness and motivation on the SCB of ship crews using the mediation mechanism of safety motivation. The research adopts a quantitative approach using a survey method and a causal design. A total of 120 crew members from passenger ships that were operating at Tanjung Priok Port in Jakarta were in the sample. The research instrument employed was a Likert scale-based questionnaire. In the Google Forms format, questionnaires were distributed via WhatsApp and email. Structured equation modeling analysis based on partial least squares (SEM-PLS) was employed to analyze the Data. The research findings show a significant correlation between safety motivation and safety awareness in ship crew SCB. Furthermore, safety awareness substantially impacts the safety motivation of the crew, and safety motivation mediates the effect of safety awareness on SCB. This evidence demonstrates the originality of the mediation concept, which posits that safety awareness impacts the SCB of passenger ship crew members through safety motivation.